Does disaster resettlement reshape household livelihood adaptive capacity in rural China? - Zhao, Tiejun; Wu, Xinyu; Cheng, Yuan; Liu, Wei (Frontiers in Sustainable Food Systems, 2024)
To bolster ecological conservation efforts and foster human well-being, the Chinese government has implemented the disaster resettlement program. Rural households encounter various environmental and social challenges regarding disaster resettlement. One of the priorities of disaster resettlement in China is to implement reforms to mitigate disaster losses and improve the livelihoods of households. The research on the livelihood adaptive capacity of households and their research framework provides a new perspective for the livelihood survey of the resettlement population. This article assesses Household Livelihood Adaptive Capacity (HLAC) and further explores how it is impacted by disaster resettlement. Taking Ankang Prefecture in Southern Shaanxi Province as a case, this study investigates the endogeneity and selection bias of resettlement. It employs the Propensity Score Matching method to empirically test the effect of disaster resettlement on household awareness, action, and ability to measure HLAC. The results show that: (1) disaster resettlement significantly reduces HLAC, and (2) poverty alleviation relocation, centralized resettlement, and short-distance relocation have a significant negative impact on HLAC. The Chinese government has tried to use disaster resettlement to address ecological protection and social development problems, and it plays a crucial role in China’s development programs. We provide evidence that disaster resettlement leads to a decrease, rather than an increase, in HLAC. Therefore, we suggest that more follow-up assistance policies should be developed to enhance HLAC.